Studi Eksperimental Pengaruh Bilangan Reynolds pada Keefektifan dan Koefisien Tekanan Penukar Panas Berkas Pipa Eliptik Susunan Berseling - Kukuh Widodo, Budi Utomo; Kamal, Samsul; ., Suhanan; Suardjaja, I Made (Jurnal Energi Dan Manufaktur, 2013)
Experimental studies have been conducted on the elliptic tube bundle with a diameter equivalent to 0.75 inches and the aspect ratio (AR) = 2.Tube bundle arranged alternate with 4-3-4 configuration and pitch lateral (SL) = 1.5 X axis major axis. Meanwhile pitch transverse (ST) varied 1.5 and 2 X minor axis. The Testing was carried out in a subsonic wind tunnel with wind speeds of 1 m / s - 12.6 m / s resulting Reynolds number Reb = 346-6904 and operating temperature 49 oC, 59 oC and 69 oC. Seven tubes inserted an electric heater produces uniform heat flux 3718 W/m2 - 3751 W/m2. The results show that the effectiveness of the heat exchanger (Q / P) varied from 3799 to 15, decreases exponentially at low Reynolds number and tends to asymptotic at Reynolds number above 1000. Meanwhile, the value pressure coefficient (?p/0.5?V2) with value 3.4-10 decreased continuously at low Reynolds numbers and asymptotic at high Reynolds number. In general, a bundle with a smaller ST has greater effectiveness and the pressure coefficient ranges is wider. Changes in operating temperature conseqwenly no effect on the effectiveness and the pressure coefficient at high Reynolds number.
Keywords: Section having an alternate elliptical tube, the effectiveness, pressure coefficient